Building individual resilience in light of declarations of the population - Magdalena Henryka Gikiewicz (Journal of Modern Science)
Objectives The purpose of the article is to present the declaration of the population in the context of building individual resilience in light of preparation for the occurrence of various types of threats, and to provide recommendations for further research on this issue.